Technology Transfer in the Ontario Harvester Industry 1830-1900 - Winder, Gordon (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1994)
ABSTRACTOntario innovation in harvesting machinery is reviewed in continental context. It is argued that rather than embedding Ontario manufacturers in technological dependence, license agreements taken out by Ontario firms with U.S. licensors transferred technology to Canadian companies. In the period 1830 to 1900 Ontario manufacturers took advantage of U.S. licenses to acquire product designs and by 1880 had mastered ownership of the designs and built the technical ability to produce their own patented designs.